First‐principles investigation of V‐doping effects on Fe3Cr4C3 carbide in hypereutectic Fe–Cr–C hardfacing coating. Issue 4 (28th July 2021) - Shi, Zhijun; Shao, Wei; Xing, Xiaolei; Ren, Xuejun; Zhou, Yefei; Yang, Qingxiang
Abstract : The crystal structure of Fe3 Cr3 VC3, obtained by V doping in Fe3 Cr4 C3, exhibits better mechanical properties. Abstract : The mechanical property improvement of M 7 C3 carbides in hypereutectic Fe–Cr–C hardfacing coating is required for its widespread application and longer service life. Vanadium is a frequently used alloying element, while the effects of V doping on the stability and tensile properties of M 7 C3 carbide have been rarely reported. In this article, the formation enthalpy, structural stability, anisotropic tensile properties and electronic structure of V‐doped M 7 C3 (Fe3 Cr4 C3 ) carbide were calculated by the first‐principles method. The mechanism by which the tensile property of Fe3 Cr4 C3 carbide can be improved by V‐atom doping is discussed. The results show that the formation enthalpy (−0.24 eV/atom) of Fe3 Cr3 VC3 carbide is lower than that (0.48 eV/atom) of Fe3 Cr4 C3 carbide, which indicates that the formation of Fe3 Cr3 VC3 carbide is more facile. The absence of an imaginary frequency in the phonon dispersion spectra reveals that the Fe3 Cr3 VC3 carbide model is stable. Compared with Fe3 Cr4 C3 carbide, the tensile strength of Fe3 Cr3 VC3 carbide in the (0001) crystal face is increased from 44.42 to 48.46 GPa and that in the (111 1) crystal face is also increased, from 28.99 to 34.19 GPa. The reasons that the tensile property of Fe3 Cr4 C3 can be improved by V doping are the electron redistribution and the formation of stronger bonds in Fe3 Cr3 VC3 carbide.